Coproporphyrin I Can Serve as an Endogenous Biomarker for OATP1B1 Inhibition: Assessment Using a Glecaprevir/Pibrentasvir Clinical Study - Hari V. Kalluri; Ryota Kikuchi; Sheryl Coppola; Jeffrey Schmidt; Mohamed‐Eslam F. Mohamed; Daniel A.J. Bow; Ahmed H. Salem (Wiley, 2021)
Organic anion transporting polypeptide (OATP) 1B1 and OATP1B3 are involved in the disposition of a variety of commonly prescribed drugs. The evaluation of OATP1B1/1B3 inhibition potential by investigational drugs is of interest during clinical drug development due to various adverse events associated with increased exposures of their substrates. Regulatory guidance documents on the in vitro assessment of OATP1B1/1B3 inhibition potential are conservative with up to a third of predictions resulting in false positives. This work investigated the utility of OATP1B1/1B3 endogenous biomarkers, coproporphyrin (CP)‐I and CP‐III, to assess clinical inhibition of OATP1B1/1B3 and potentially eliminate the need for prospective clinical drug‐drug interaction (DDI) studies. Correlations between CP‐I exposures and various OATP1B1 static DDI predictions were also evaluated. Glecaprevir/pibrentasvir (GLE/PIB) 300/120 mg fixed‐dose combination is known to cause clinical inhibition of OATP1B1/1B3. In a clinical study evaluating the relative bioavailability of various formulations of GLE/PIB regimen, CP‐I peak plasma concentration (Cmax) ratio and 0-16‐hour area under the concentration‐time curve (AUC0-16) ratio relative to baseline increased with increasing GLE exposures, whereas there was a modest correlation between GLE exposure and CP‐III Cmax ratio but no correlation with CP‐III AUC0-16 ratio. This suggests that CP‐I is superior to CP‐III as an endogenous biomarker for evaluation of OATP1B1 inhibition. There was a significant correlation between CP‐I and GLE Cmax (R2 = 0.65; P < 0.001) across individual subjects. Correlation analysis between GLE OATP1B1 R values and CP‐I exposures (Cmax ratio and AUC0-16 ratio) suggests that an R value of > 3 can predict a biologically meaningful inhibition of OATP1B1 when the inhibitor clinical pharmacokinetic parameters are available.